Leadership styles as predictors of work attitudes: A moderated-mediation link - Or Shkoler; Aharon Tziner (Amfiteatru Economic Journal, 2020)
Drawing on the recent locus and mechanism models of leadership (Eberly, Johnson, Hernandez & Avolio, 2013), the purpose of this paper is to begin to explore the role of leadership styles from two different loci standpoints - (1) dyadic-focused, transformational leadership; and (2) leader-focused, transactional leadership-as important antecedents to individual and organizational outcomes in the organizational context. Among employees in several organizations in Israel (N=265), we investigated the relationships between (1) several individual and organizational work outcomes (i.e., job engagement, work enjoyment); and (2) the two leadership styles (the predictors, namely, transformational and transactional leadership). In addition, we explored the roles of (3) a possible mediational mechanism through which we posited the leadership styles operate (i.e., work drive); and (4) a possible moderator (i.e., organization types). These associations were presented as a model that was both tested via multi-group moderation structural equation modeling (SEM) and through moderated-mediation analyses via competing models of demographical differences. The findings illustrated that both transformational and transactional leadership styles have a direct, positive influence on outcomes. However, with regard to the intermediary moderator and mediator variables, the results demonstrate varied and interesting relationships in current study, the indication being that each of the two leadership styles, when interfacing with unique combinations of moderator and mediator, produce outcomes specific to the leadership style. Important concepts, recommendations, and implications are discussed.
Keywords: I15; Q53; Q57; C38; 330; transformational-transactional leadership; job engagement; organization types; moderation-mediation